Problemy przebudowy strukturalnej rolnictwa polskiego w latach 1926-1930. Program agrarny Witolda Staniewicza - Łapa, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 1999)
The agrarian question was one of the main problems of the economy of the Second Republic of Poland (1918-1939). Witold Staniewicz – the minister of the agrarian reform – was the creator of the agrarian program which was based on the agrarian act of December 28th 1925. According to this act the government should have realised the following tasks: an integration of the separate pieces of land of the same owner into a whole, an aggrandizement of the smallholdings, the state’s credits for the agriculture, a creation of the new farms with the land of parcelled out of the great property, a settlement action on the eastern borderlands of Poland, an arrangement of the melioration, and a regulation of the easements. In the years 1926-1930 a parcelling out of a great property, a liquidation of the servitudes, an integration of the lands, and the other works which influenced the agrarian structure of the country were completed quicker than before. They were realised in a moderate still consequent way. A good conjuncture in agriculture that had lasted since 1928 favoured the realisation of such a policy. Still in the following years, the diminution of sum spending on those purposes slopped that activity.